Foundations of Evidence-Based Medicine Clinical Epidemiology and Beyond - Jenicek, Milos 1935- (CRC Press LLC, 2019)
This comprehensive text focuses on reasoning, critical thinking and pragmatic decision making in medicine. Based on the author's extensive experience and filled with definitions, formulae, flowcharts and checklists, this fully revised second edition continues to provide invaluable guidance to the crucial role that clinical epidemiology plays in the expanding field of evidence-based medicine. Key Features: Considers evidence-based medicine as a universal initiative common to all health sciences and professions, and all specialties within those disciplines Demonstrates how effective practice is reliant on proper foundations, such as clinical and fundamental epidemiology, and biostatistics Introduces the reader to basic epidemiological methods, meta-analysis and decision analysis Shows that structured, modern, argumentative reasoning is required to build the best possible evidence and use it in practice and research Outlines how to make the most appropriate decisions in clinical care, disease prevention and health promotion Presenting a range of topics seldom seen in a single resource, the innovative blend of informal logic and structured evidence-based reasoning makes this book invaluable for anyone seeking broad, in-depth and readable coverage of this complex and sometimes controversial field